Organizational Design Analysis of Telkomedika and It’s Impact on the Effectiveness of Corporate Health Services - Diona Wahyuni; Rinawati (Penerbit Jurnal Indonesia, 2026)
This study aims to comprehensively analyze the organizational design implemented by Telkomedika, one of the corporate healthcare providers in Indonesia, and evaluate its impact on service effectiveness. The research focuses on several key elements of organizational design, such as structural differentiation, integration mechanisms, centralization and decentralization of decision-making, the level of formalization, and the suitability of the organizational structure based on mechanistic and organic theories. The method used in this study is a descriptive qualitative approach, with data collection techniques including in-depth interviews, field observations, and a review of internal organizational documents. The results indicate that Telkomedika has a fairly high level of horizontal and vertical differentiation, but integration and coordination between units is still suboptimal. The decision-making process remains centralized, which can hinder the speed and flexibility of services, particularly in emergencies or cases requiring rapid decisions. Telkomedika's current organizational structure reflects mechanistic rather than organic characteristics, despite the demands of corporate healthcare services for high adaptability, flexibility, and speed of response. Therefore, a structural transformation toward a more adaptive, collaborative, and technology-based organizational model is needed to sustainably improve the effectiveness and competitiveness of corporate healthcare services.